TINJAUAN YURIDIS TERHADAP PENGEMIS DAN GELANDANGAN DI KOTA PALEMBANG - dewi, mulyati (Solusi, 2025)
This research will discuss problems that will have negative impacts if the problems of beggars and vagrantsare not quickly resolved. These are because the ways in which homeless people and beggars make a living mostly disturb the community so that the impact includes disrupting public order, cleanliness, the beauty of the city, security and order as well as disrupting population data in the area where they live. Furthermore, regarding the criminal threat that can be imposed on beggars and vagrants based on Articles 504 and 505 of the Criminal Code. It can be threatened with imprisonment for six weeks if it is carried out in public and the threat of imprisonment for a maximum of three months if the vagrancy is carried out by three or more people who are aged minimum sixteen years.